Hybrid modelling of discrete-continuous interfaces in mining systems - Passos, Lúcio Fábio Dias; Mota, Thalles Vinicius Frade; Conceição, Samuel Vieira; Torres Jr., Noel; Almeida, João Flávio de Freitas (Brazilian Journal of Production Engineering, 2026)
Mining supply chains often involve interfaces between discrete and continuous processes, such as the interaction between mine truck traffic and crushing systems, where operational variability can propagate through production stages and affect system performance. However, most studies analyze these subsystems separately, with little attention to the integrated dynamics between discrete and continuous processes, present at various points along the production chain. This study investigates the propagation of variability at the mine-plant interface of an iron ore mining and processing plant, using a hybrid modeling framework that combines discrete event simulation (DES) and analytical queuing models. The DES component represents the stochastic dynamics of mine operations, while an analytical G/G/1/b model evaluates the behavior of the downstream crushing system. The models are calibrated using 13 months of operational data and applied to evaluate alternative operational plans, including fleet expansion, safety stock implementation, and micro-downtime reduction. The study demonstrates that a hybrid modeling approach provides an effective and scalable solution for analyzing the propagation of variability in complex mining systems with discrete-continuous interfaces.
Keywords: Simulação híbrida; Propagação da variabilidade; Simulação de eventos discretos; Cadeia de Suprimento de Mineração